MHD Boundary Layer Flow of Micropolar Fluids due to Porous Shrinking Surface with Viscous dissipation and Radiation - Waqas, H.; Hussain, S.; Khalid, S. (The Nucleus, 2021)
The mathematical analysis and numerical solution for the flow of micropolar fluids owing to shrinking boundary is considered in the presence of magnetic field and thermal radiation. The parametric study of the problem demonstrates the effects of magnetic field, suction, micropolar material parameter and thermal radiation on velocity, microrotation and temperature. The mathematical model of the problem is transformed to non-dimensional form to obtain numerical solution. The results have been obtained for several representative values of the material parameters d1, d2 and d3, heat source parameter l and magnetic parameter M, suction/injection parameter S, Eckert number Ec, Radiation parameter Rn and Prandtl number Pr . The flow speed and microrotation are slowed with incremented inputs of micropolar parameter d1. The fluid temperature increases with radiation parameter but it diminishes against suction.